Prevalensi dan Derajat Infeksi Cacing Saluran Pencernaan pada Itik Jawa (Anas javanica) di Dua Daerah Geografis Berbeda - Dian Ayu Permatasari; Kusriningrum Rochiman; Tjuk Imam Restiadi; Sri Mumpuni Sosiawati; Endang Suprihati; Mustofa Helmi Effendi (Journal of Parasite Science (JoPS), 2020)
The aim of this study was to determined the prevalence and infection disease degree of worm gastrointestinal on duck in two different geographical territories. The duck feces examination samples were using natif method, sedimentation, and floatation. The result of this examination of lowlands showed that 20% (12/60) ducks checked that infected by two worm species of nematoda, wich ia Ascaridia galli (11,7%), Heterakis sp. (8,3%), with the range of infection degree classified as low infection (0-500 EPG), while the examination results of highlands showed that 44% (33/75) ducks checked infected by two worm species of nematoda, which is Ascaridia galli (17,3%), Heterakis sp. (10,7%) and one species of trematoda, which is Echinostoma sp. (6,7%), with the range infection degree classified low infection (0-500 EPG). it can get both single or mix infection. The analysis result has shown that there was differences between lowlands and highlands on the prevalence and infection disease degree of worm gastrointestinal on duck, was highly significant (p<0,05).